Effects of carbonated liquid on swallowing dysfunction in dementia with Lewy bodies and Parkinson’s disease dementia - Larsson V (Dove Medical Press, 2017)
Victoria Larsson,1 Gustav Torisson,1,2 Margareta Bülow,3 Elisabet Londos1 1Clinical Memory Research Unit, Department of Clinical Sciences Malmö, Lund University, 2Department of Infectious Diseases, 3Diagnostic Centre of Imaging and Functional Medicine, Skåne University Hospital, Malmö, Sweden Background: Swallowing dysfunction is an increasingly recognized problem in patients with dementia with Lewy bodies (DLB) and Parkinson’s disease dementia (PDD), which can result in aspiration pneumonia and death. Few studies have examined potential ways of improving swallowing function in this fragile patient group. The aim of this study was to evaluate swallowing dysfunction and carbonated liquid using videofluoroscopy in DLB and PDD patients. Methods: A total of 48 patients with DLB and PDD were referred for a clinical examination with videofluoroscopy. Descriptive overall assessments were provided at the time of the examination regarding swallowing function and the effects of different modifications, including carbonated thin liquid (CTL). Additionally, a repeated measures quantitative retrospective analysis has been performed comparing 1) thin liquids; 2) thickened liquids and 3) CTLs, with regard to the quantitative variables 1) pharyngeal transit time (PTT); 2) pharyngeal retention and 3) tracheal penetration. Results: In all, 40/48 (83%) of the patients had a swallowing dysfunction, which was confirmed on videofluoroscopy, with 34/40 (85%) patients having a pharyngeal-type dysfunction. A total of 14/40 (35%) patients with an objective swallowing impairment did not have any subjective swallowing symptoms. Out of the patients with swallowing dysfunction, 87% had an overall improved swallowing function with carbonated liquid. PTT for carbonated liquid (median 633 ms, interquartile range [IQR] 516–786 ms) was quicker than for thin liquid (760 ms, IQR 613–940 ms, P=0.014) and thickened liquid (880.0 ms, IQR 600–1,500 ms, P<0.001). No significant effect was seen in residue or penetration. Conclusion: The majority of patients with DLB or PDD had a swallowing dysfunction, sometimes without subjective swallowing symptoms, which improved with carbonated liquid. This highlights the importance of investigating patients with videofluoroscopy and to carry out a prospective interventional study to further evaluate carbonated liquid, also addressing the effects on quality of life, aspiration and mortality. Keywords: therapeutics, video recording, deglutition, dysphagia, carbonated beverages, swallowing disorders